Nationwide multi-institutional retrospective analysis of high-dose-rate brachytherapy combined with external beam radiotherapy for localized prostate cancer: An Asian Prostate HDR-BT Consortium - Ishiyama, Hiromichi; Kamitani, Nobuhiko; Kawamura, Hidemasa; Kato, Shingo; Aoki, Manabu; Kariya, Shinji; Matsumura, Taisei; Kaidu, Motoki; Yoshida, Ken; Hashimoto, Yaichiro; Noda, Yasutaka; Lim, Keith H.C.; et al. (Brachytherapy, 2017)
To report outcomes and risk factors of high-dose-rate (HDR) brachytherapy combined with external beam radiotherapy with or without androgen deprivation therapy (ADT) in prostate cancer patients. This multi-institutional retrospective analysis comprised 3424 patients with localized prostate cancer at 16 Asian hospitals. One-thirds (27.7%) of patients received only neoadjuvant ADT, whereas almost half (49.5%) of patients received both neoadjuvant and adjuvant ADT. Mean duration of neoadjuvant and adjuvant ADT were 8.6 months and 27.9 months, respectively. Biochemical failure was defined by Phoenix ASTRO consensus. Biochemical control rate, clinical disease-free survival (cDFS), cause-specific survival, and overall survival (OS) were calculated. Median followup was 66 months. Ten-year biochemical control, cDFS, cause-specific survival, and OS rate were 81.4%, 81.0%, 97.2%, and 85.6%, respectively. Receiving both neoadjuvant and adjuvant ADT was detected as a favorable factor for biochemical control, cDFS, and OS, but pelvic irradiation was detected as an adverse factor for cause-specific survival, and OS. Ten-year cumulative rates of late Grade ≥2 genitourinary and gastrointestinal toxicities were 26.8% and 4.1%, respectively; receiving both neoadjuvant and adjuvant ADT was detected as a favorable factor for preventing both toxicities. HDR combined with external beam radiotherapy was an effective and safe treatment for localized prostate cancer. Combination of long-term ADT was suggested to be necessary, even for HDR brachytherapy, and was useful in suppressing late toxicities. Meanwhile, pelvic irradiation was suggested to have an adverse effect on OS of our study population.